Antithrombotic Therapy for Inferior Vena Cava Stenting of Malignant Inferior Vena Cava Syndrome: A Questionnaire Study of Japan Interventional Radiology Study Group (JIVROSG) - Mizuki Ozawa; Miyuki Sone; Shunsuke Sugawara; Yasuaki Arai; Masahiko Kusumoto (The Arab Journal of Interventional Radiology)
Purpose The aim of this study was to evaluate the differences in antithrombotic therapy policies for inferior vena cava (IVC) stent placement among institutions and interventional radiologists in Japan.